Using the TIDieR Checklist to Standardize the Description of a Functional Strength Training Intervention for the Upper Limb After Stroke. Issue 3 (July 2016) - van Vliet, Paulette; Hunter, Susan M.; Donaldson, Catherine; Pomeroy, Valerie
Abstract : Background and Purpose: Published reports of intervention in randomized controlled trials are often poorly described. The Template for Intervention Description and Replication (TIDieR) checklist has been recently developed to improve the reporting of interventions. The aim of this article is to describe a therapy intervention used in the stroke rehabilitation trial, "Clinical Efficacy of Functional Strength Training for Upper Limb Motor Recovery Early After Stroke: Neural Correlates and Prognostic Indicators" (FAST-INdICATE), using TIDieR. Methods: The functional strength training intervention used in the FAST-INdICATE trial was described using TIDieR so that intervention can be replicated by both clinicians, who may implement it in practice, and researchers, who may deliver it in future research. The usefulness of TIDieR in the context of a complex stroke rehabilitation intervention was then discussed. Results and Discussion: The TIDieR checklist provided a systematic way of describing a treatment intervention used in a clinical trial of stroke rehabilitation. Clarification is needed regarding several aspects of the TIDieR checklist, including in which section to report about the development of the intervention in pilot studies, results of feasibility studies; overlap between training and procedures for assessing fidelity; and where to publish supplementary material so that it remains in the public domain. Conclusions: TIDieR is a systematic way of reporting the intervention delivered in a clinical trial of a complex intervention such as stroke rehabilitation. This approach may also have value for standardizing intervention in clinical practice. Video abstract available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A131 ). Abstract : Supplemental Digital Content is Available in the Text.